Development of methods of the international division of labor - Mekhovich, S. A.; Pererva, P. G.; Tyufanov, G. L. (My University, 2023)
The report proves that the international exchange of goods, services, technologies, the international movement of capital and labor increasingly determine the development of both the world economy as a whole and its subjects - individual countries. The division of labor is a system of social labor determined by the course of history itself. It develops as a result of the qualitative differentiation of labor activity in the process of the development of society and exists in various forms.
Розвиток методів міжнародного поділу праці
Keywords: international activity; division of labor; employment; labor market